2020
DOI: 10.1128/msystems.00765-19
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat/High-Protein, Atkins-Type Diet Exacerbates Clostridioides ( Clostridium ) difficile Infection in Mice, whereas a High-Carbohydrate Diet Protects

Abstract: Clostridioides difficile (formerly Clostridium difficile) infection (CDI) can result from the disruption of the resident gut microbiota. Western diets and popular weight-loss diets drive large changes in the gut microbiome; however, the literature is conflicted with regard to the effect of diet on CDI. Using the hypervirulent strain C. difficile R20291 (RT027) in a mouse model of antibiotic-induced CDI, we assessed disease outcome and microbial community dynamics in mice fed two high-fat diets in comparison wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 68 publications
(62 reference statements)
4
42
0
Order By: Relevance
“…Because of C. difficile's ability to ferment amino acids as a nutrient source, dietary protein may also play a role in C. difficile pathogenesis. A recent study found that a high-fat/high-protein diet intensified C. difficile proliferation and virulence in a mouse model of infection (117). This study also supported the protective role of a high-carbohydrate diet.…”
Section: Factors Shaping C Difficile Epidemiology and Pathogenesissupporting
confidence: 71%
“…Because of C. difficile's ability to ferment amino acids as a nutrient source, dietary protein may also play a role in C. difficile pathogenesis. A recent study found that a high-fat/high-protein diet intensified C. difficile proliferation and virulence in a mouse model of infection (117). This study also supported the protective role of a high-carbohydrate diet.…”
Section: Factors Shaping C Difficile Epidemiology and Pathogenesissupporting
confidence: 71%
“…Other results have shown that feeding a high-fat diet coincident with antibiotic treatment increases susceptibility to CDI [76,77]. The regimen used in our studies was distinct from those previously described.…”
Section: Discussionmentioning
confidence: 91%
“…Pupfish were either left untreated ( n = 12) or exposed ( n = 12) to a cocktail of kanamycin (400 μg • ml − 1 ), gentamicin (35 μg • ml − 1 ), colistin (850 IU • ml − 1 ), metronidazole (215 μg • ml − 1 ), and vancomycin (45 μg • ml − 1 ) for 48 h prior to oxygen consumption measurement. This combination of broad-spectrum antibiotics acting on protein synthesis (kanamycin and gentamicin), cell membrane integrity (colistin), DNA synthesis (metronidazole) and peptidoglycan synthesis (vancomycin) is often used to deplete the mouse gut microbial community to study Clostridioides difficile infections and is highly effective [ 28 ].…”
Section: Methodsmentioning
confidence: 99%